Relações entre as dimensões motivação para viajar, fontes de informação utilizadas e qualidade percebida dos serviços por turistas de festivais: um estudo sobre a Oktoberfest de Blumenau e de Munique - Zucco, Fabricia Durieux (2012)
In Brazil, tourism events are on the rise especially the festivals that help to promote, to enhance and to preserve the tourism, cultural, historical and environmental heritage from a specific location. A very representative example is the Oktoberfest in Blumenau, the biggest festival of the German tradition of the country, a compound of fun, folklore and cultural richness, reveal the passion for music, dances and German cuisine. Its inspiration the Oktoberfest in Munich, already aging two hundred years of tradition, is considered the largest beer festival in the world and has great economic importance to the region. The understanding of the phenomena which govern the management of tourism products has been the focus of several academic papers and three approaches are worth mentioning from the viewpoint of the tourist: motivation to travel, sources of used information and perceived quality of service. No studies dedicated to understanding the decision processes of tourists from the relationships between these three dimensions were found. Moreover, there are no studies comparing the two Oktoberfest editions. This thesis aims to contribute to filling in this gap through the following research question: what are the relationships between the dimensions of motivation to travel, sources of used information and perceived quality of service through the tourist s perspective visiting the Oktoberfest in Blumenau (BR) and Munich (DFR)? A number of fourteen hypotheses were drawn to try to meet this goal. The methodological procedures occurred in two phases: firstly qualitative, through interviews with the event managers in Munich and in Blumenau, bringing up results which will allow the survey instrument refining. And apart from that, 285 valid interviews were collected in Munich and 432 in Blumenau for a quantitative approach. The scales were validated with acceptable indicators and tests showed a higher tendency of the sample agreed with the construct Informal of Dimension Information Sources Used and the Brazilian sample with all the scales. The dimension called Information Sources Used was the one which brought more surprises, as results showed Formal traditional media (e.g., radio and TV) overcame by travel agencies, brochures and advertising material in the hotels. There was rejecting measuring their choices of meals and snacks, beer and music shows, and attractions in the dimension Perceived Quality of Services. This is the dimension that matters the most to the managers and certainly characterized by becoming the investigation s best contribution to the management study field. The major limitation of this study was its sample of non-probabilistic convenience which prevents the result s universalization. The managerial implications are substantial, pointing out the overlap between the three dimensions in a chain of cause and effect which indicates the need for it to work seamlessly, as in the dissemination of tourist destination or in the research facilitation in information sources. The implications for academic studies are related to the importance to further investigate the events and festivals so abundant in Brazil creating an inventory of information which will certainly inspire researchers to advance knowledge about this promising field.